Biotechnology Applications of Microalgae (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, “Biotechnology Applications of Microalgae”, is focused on the latest novel advances related to the production of different bioactive compounds from microalgae and their biotechnological use.